ANALISIS KONFLIK NDUGA DARI PERSPEKTIF MAHASISWA UKSW ASAL PAPUA DAN DAMPAKNYA TERHADAP PERLINDUNGAN HAM - Yakomina Yohana Andatu; Nani Mediatati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the perspectives of Satya Wacana Christian University (UKSW) students from Papua on the armed violence conflict that occurred in Nduga, Papua Mountains, and its impact on the protection of human rights in the area. The research method used is qualitative with an in-depth interview approach to collect data from students who have a background and direct experience related to the conflict. The results showed that students had diverse views on the causes and impacts of the conflict, including the political, economic and social factors that contributed to the tensions in Nduga. In addition, students also highlighted the negative impact of the conflict on human rights protection, such as violations of the right to life, the right to education, and the right to health. Recommendations resulting from this research include the need for dialogue between conflicting parties, increasing the role of the government in protecting the community.